Platelet-rich plasma in dermatology and aesthetic medicine - Ochyra, Łukasz; Łopuszyńska, Anna (Quality in Sport, 2024)
Introduction and purpose Aesthetic medicine is one of the youngest fields of medicine. Initially, it focused on improving the quality of life of patients by using various treatments aimed at stopping the aging process. Over time, this branch of medicine has developed dynamically, and nowadays the treatments focus not only on improving the appearance of the skin and its defects, but are also used to treat many dermatological problems. Platelet-rich plasma (PRP) is an autologous concentrate of platelets in a small volume of plasma. having numerous applications in many fields of medicine. The aim of this work is to present the method, focusing on its positive effects in the problems of aesthetic and regenerative medicine, as well as in some dermatological diseases. Material and methods The review was baised on the articles obtained from Pubmed and Google Scholar scientific databases from recent years using the keywords: aesthetic medicine, platelet-rich plasma, dermatology. Results The presence of numerous growth factors and other active ingredients makes the action of PRP comprehensive and based on several mechanisms. Studies show a positive effect, especially in skin rejuvenation and anti-aging prevention, hair reconstruction, wound healing and reconstruction of scars of various etiologies, as well as in pigmentation disorders. Moreover, combining PRP with other methods such as laser therapy or microneedling produces a synergistic effect, improving overall treatment results. Conclusions Platelet-rich plasma is an autologous preparation obtained after centrifugation of blood collected from the patient. The properties of PRP make it widely used in many clinical situations. is used both in aesthetic medicine and in dermatological problems. It should be emphasized that further multi-center studies are needed to standardize treatment protocols and adapt them to specific problems. Keywords: aesthetic medicine, platelet-rich plasma, dermatology.